AKUNTABILITAS KEUANGAN MELALUI OPTIMALISASI SISKEUDES DAN KECAKAPAN PENGELOLA KEUANGAN DESA DI KECAMATAN BLANG MANGAT - Fakriah, Fakriah; Lukman, Lukman; Halimatus Sa’diyah, Halimatus Sa’diyah (Ekonis: Jurnal Ekonomi dan Bisnis, 2024)
Abstract— This study aims to analyze the effect of optimizing the financial information system and village apparatus competency on financial accountability in managing village funds in Blang Mangat District, Lhokseumawe City. The study population includes village apparatus who are directly or indirectly involved in managing village finances, such as village heads, village secretaries, treasurers, village operators, heads of development affairs, and hamlet/RT heads. Sampling was carried out purposively based on the criteria of involvement in village financial management. The research variables include optimizing the financial information system (X1), village apparatus competency (X2), and financial accountability in managing village funds (Y). This study uses a quantitative descriptive approach with multiple linear regression analysis through the SPSS application. The classical assumption test shows that the data is normally distributed. The results of the partial analysis show that optimizing the financial information system and village apparatus competency have a positive and significant effect on financial accountability. Simultaneously, both independent variables have positive effect on the dependent variable. The determination test shows that the contribution of optimizing the financial information system and village apparatus competency to financial accountability is 11%, while the other 89% is influenced by other factors. These results indicate that the influence of independent variables on financial accountability is strong.Keywords— Accountability, Siskeudes, Optimization, Village Finance